2019
DOI: 10.1017/bsl.2019.59
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Realizability Results With Classical Constructions

Abstract: J.L. Krivine developed a new method based on realizability to construct models of set theory where the axiom of choice fails. We attempt to recreate his results in classical settings, i.e. symmetric extensions. We also provide a new condition for preserving well-ordered, and other particular type of choice, in the general settings of symmetric extensions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Thanks to Asaf Karagila for several fruitful discussions [Kar19]. He observed that, by exactly the same method, we obtain a program, not only for AC, but for every axiom which can be shown compatible with ZFC by forcing (Theorem 5.7); for instance CH, 2 β„΅ 0 = β„΅ 2 + Martin's axiom, etc.…”
Section: Introductionmentioning
confidence: 90%
“…Thanks to Asaf Karagila for several fruitful discussions [Kar19]. He observed that, by exactly the same method, we obtain a program, not only for AC, but for every axiom which can be shown compatible with ZFC by forcing (Theorem 5.7); for instance CH, 2 β„΅ 0 = β„΅ 2 + Martin's axiom, etc.…”
Section: Introductionmentioning
confidence: 90%
“…If we then take the direct limit of this sequence, we end up with an ill-founded structure. 13 To avoid this, we want to make it impossible for such ill-founded structures to result from taking these natural limits. To do this, we would like to be able to track all of the possible evolutions and ensure that we will always evolve a wellfounded structure.…”
Section: (𝑝) ⟢ 𝛾 𝑝 𝐹(𝑝) βˆ‹ 𝐺(𝑝) = 𝛾 𝑝 (βˆ…) ↓ Idmentioning
confidence: 99%
“…12 I.e., the submodel of 𝐹(π‘ž) generated by the pointwise image of 𝐹(𝑝) through 𝐹(≀ 𝑝,π‘ž ) is isomorphic to 𝐹(𝑝). 13 More specifically, if lim β†’ 𝐹 = lim β†’ ⟨⟨𝐹(𝑝 𝑛 )⟩, ⟨𝐹(≀ 𝑝 𝑛 ,𝑝 π‘š )⟩ π‘›β‰€π‘šβˆˆπœ” ⟩ = βŸ¨π‘€ ∞ , 𝐸 ∞ ⟩, then 𝐸 is ill-founded on 𝑀. To see this let 𝑔 𝑛,∞ ∢ 𝐹(𝑝 𝑛 ) β†’ 𝑀 ∞ be the canonical map from 𝑀 into the limit.…”
Section: (𝑝) ⟢ 𝛾 𝑝 𝐹(𝑝) βˆ‹ 𝐺(𝑝) = 𝛾 𝑝 (βˆ…) ↓ Idmentioning
confidence: 99%
See 1 more Smart Citation